Probability of induced extreme precipitation events in Central America due to tropical cyclone positions in the surrounding oceans - Hidalgo León, Hugo G. (2022)
The preparedness of national and local authorities for extreme hydrometeorological events could alleviate the impacts in many socioeconomical sectors. A statistical tool for the prediction or assessment of extreme precipitation probabilities caused by the presence of Tropical Cyclones (TCs) in the surrounding oceans of Central America is presented. The model is based in ftting precipitation probability distributions associated with the location of the TCs. The probabilities of medium, high, and very high levels of extreme rain and associated with the observed precipitation of the 60, 75, and 90 percentiles, are displayed in a map which can be used (with other tools) to issue alerts by emergency and response authorities. Impacts related to TCs can be classifed in direct or indirect. In the case when the TCs are located in the Caribbean/Atlantic basin, there is a critical confguration near the Gulf of Honduras that drives both high probabilities of direct (in the northern countries) and indirect (in the southern countries) extreme precipitation. In the Eastern Tropical Pacifc TC locations, probabilities of indirect impacts are usually lower than for the Caribbean/Atlantic. This is related to the usual trajectories in this former basin, that move away from the continent. Both, in Caribbean/Atlantic and Eastern Tropical Pacifc’s TCs, the probabilities of indirect efects usually are higher in the Pacifc slope of the isthmus than in the Caribbean. Here we present one tool that can be used with others analyses by emergency ofcials to determine the locations where alerts of extreme weather must be issued to prevent human life’s lost.